Bladder leiomyoma presenting as dyspareunia: Case report and literature review. Issue 28 (July 2016) - Xin, Jun; Lai, Hai-ping; Lin, Shao-kun; Zhang, Qing-quan; Shao, Chu-xiao; Jin, Lie; Lei, Wen-hui
Abstract: Introduction: Leiomyoma of the bladder is a rare tumor arising from the submucosa. Most patients with bladder leiomyoma may present with urinary frequency or obstructive urinary symptoms. However, there are a few cases of bladder leiomyoma coexisting with uterine leiomyoma presenting as dyspareunia. We herein report an unusual case of coexisting bladder leiomyoma and uterine leiomyoma presenting as dyspareunia. Case presentation: A 44-year-old Asian female presented to urologist and complained that she had experienced dyspareunia over the preceding several months. A pelvic ultrasonography revealed a mass lesion located in the trigone of urinary bladder. The mass lesion was confirmed on contrast-enhanced computed tomography (CT). The CT scan also revealed a lobulated and enlarged uterus consistent with uterine leiomyoma. Then, the biopsies were then taken with a transurethral resection (TUR) loop and these biopsies showed a benign proliferation of smooth muscle in a connective tissue stroma suggestive of bladder leiomyoma. An open local excision of bladder leiomyoma and hysteromyomectomy were performed successfully. Histological examination confirmed bladder leiomyoma coexisting with uterine leiomyoma. Conclusion: This case highlights a rare presentation of bladder leiomyoma, dyspareunia, as the chief symptom in a patient who had coexisting uterine leiomyoma. Bladder leiomyomas coexisting with uterine leiomyomas are rare and can present with a wide spectrum of complaints including without symptoms, irritative symptoms, obstructive symptoms, or even dyspareunia.